Vigencia del libro de texto ante las tic - Ortega Quituisaca, Frank Erick (Machala, 2019)
This descriptive research with quantitative-qualitative approach was made with the aim of arguing from the perspective of teachers and students, the use of the textbook against other technological resources in the teaching-learning process of the Educational Unit Juan Pablo II; It was systematized through bibliographic review methods, content analysis, analytical-synthetic, statistical and data triangulation; as well as the application of survey and interview techniques. The results obtained reveal that the textbook, despite the restrictions imposed on the teacher and the benefits of digital media is still in force. For the full implementation of ICT it is necessary to overcome existing subjective and objective limitations
Esta investigación descriptiva con enfoque cuanti-cualitativo se realizó con el objetivo de argumentar desde la perspectiva del profesorado y alumnado, el uso del libro de texto frente a otros recursos tecnológicos en el proceso de enseñanza-aprendizaje de la Unidad Educativa Juan Pablo II; fue sistematizada a través de los métodos revisión bibliográfica, análisis de contenido, analítico-sintético, estadístico y triangulación de datos; así como de la aplicación de las técnicas encuesta y entrevista. Los resultados obtenidos develan que el libro de texto, a pesar de las restricciones que imponen al docente y los beneficios de los medios digitales aún se encuentra vigente. Para la plena implementación de las TIC es necesario superar las limitaciones subjetivas y objetivas existentes.
Keywords: LIBRO DE TEXTO; DOCENTE; TECNOLOGIA